Procedimentos realizados em pacientes near miss neonatal internados em UTIN de risco habitual - Santana, Vinícius Santos (2018)
Infant mortality still remains one of the greatest public health problems in the world today. Over the years, Brazil has shown a significant decrease in infant mortality rates, which is even more striking in North and Northeast regions. The concept of near miss neonatal (NMN) has been a useful tool for assessing the quality of neonatal health care and indicating ways to reduce mortality in the first month of life. Advances in intensive care in neonatal intensive care units in preterm infants have also shown a decline in neonatal mortality over the years. The present study aims to describe the therapeutic interventions of neonates near miss neonatal admitted to a Neonatal Intensive Care Unit. A cohort study was carried out in a maternity clinic at Aracaju, Sergipe, Brazil, in which cases of NMN were identified and data on gestation, delivery and hospitalization at the Neonatal Intensive Care Unit were collected through interviews and medical records. Twenty-five newborns were evaluated during the period from March/2015 to September/2015. The results point to the great use of interventions in the NICU, mainly in relation to the use of antibiotics and oxygen therapy, and the practice of blood transfusion was not observed during this period. Therapeutic procedures such as antibiotic therapy, umbilical catheterization and cardiopulmonary resuscitation rates presented similar rates to previous studies.